EXPLORING DNA TECHNIQUE IN CRIME INVESTIGATION IN THE BACKGROUND OF OTHER SCIENTIFIC METHODS - Pervez, Anjum; Verma, Dr Sandhya (International Journal of Psychosocial Rehabilitation, 2020)
One of the most significant inventions and development in the history of the human race is forensic science. Without having knowledge of forensic science, there would be a great effect on the society as well as the judicial system. At contemporary era forensic science plays a very vital role in solving the crime problem. It provides the best opportunities to the judicial system for solving the crime and in detection the criminal. Even though the forensic science is being not so new discipline, not many people are aware about it. In old time due to absence of technological development, it was never felt by the judicial system that forensic science techniques needed to be apply because the old methods were taking into consideration for committing the crime. Approximately before two thousand year the crimes were solved on the behalf of debate and argument made by the parties. On the behalf of the argument and debate made by the parties, the public held the power to decide whose arguments are legit. The old techniques of crime detection and solving the crime problem were sufficient to the criminal justice system. But by the passage of the time new techniques emerge due to vast technological development and the criminal became aware towards the use of these technologies in the commission of crime. The accused persons were getting the benefit of the technological development. Now a day it became very easy to be safe from any criminal liability. It was the great challenge before the court to find out the crime and to punish the accused by applying the old techniques. The accused person was taking benefit of this kind of lack of proper knowledge about the forensic. So there felt dire need to apply a such technique which could solve this great problem and proper justice could be provided to the victim as well as society. By the passing of the time the judiciary started to take the interest in application of the scientific techniques. And till now various decisions on the behalf of these scientific techniques has been passed by the judiciary successfully. And it becomes possible to control the commission of the crime. The present judicial system of India comprises various modes of techniques including DNA Profiling, Brain-Fingerprinting, Narco-Analysis, Polygraph, DNA Fingerprinting, forensic DNA etc which is proving veryhelpful in solving the crime problem. At present courts are taking these techniques into consideration while delivering judgments. In future it would impossible to solve the crime and to find out the criminal without applying these techniques. Day by day the new technological developments take place. So there is a need to apply to such techniques so that the society could be protected from the commission of the crime and if crime commit by any person, he could be punished. Even though these scientific techniques are proving very helpful asset to the society as well as the criminal justice system, but there are also some bad consequences of the application of these techniques. Little bit temperament with the scientific evidence reverse the result of a finding of the crime. By the present article the effort has been made to disclose the relevancy of the techniques of forensic science as well as their bad consequences if not conducted with care.